Soul mountain - Gao, Xingjian 1940- (HarperCollins, 2000)
A man's journey in the remote areas of southwest China mirror his inner search of "Soul Mountain".
Keywords: Geschichte 1983; Meaning (Philosophy) -- Fiction; Reise; Schriftsteller; Selbstreflexion; China; Fiktionale Darstellung